The role of antenatal relaxation practices in enhancing maternal psychological wellbeing and childbirth experiences: an observational study - Mo Tabib; Mo Tabib; Tracy Humphrey; Katrina Forbes-McKay (Frontiers in Global Women's Health)
IntroductionThere is growing qualitative evidence that antenatal education on relaxation practices can enable women to deliberately induce a deep state of emotional calmness. Learning to shift focus from distressing emotions such as anxiety and fear to this altered state of calmness may significantly enhance women's confidence, thereby protecting maternal psychological wellbeing and leading to more positive childbirth experiences. However, the generalisability of these findings remains uncertain. This study aimed to bridge this gap by using quantitative methods to validate and extend the qualitative evidence.MethodsThrough an observational study with a prospective longitudinal cohort design, ninety-one women attending a single antenatal relaxation class at a Scottish NHS maternity service completed online surveys including Childbirth Self-Efficacy Inventory (CBSEI), Warwick Edinburgh Mental Well-Being Scale (WEMWBS), Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ), and Six-item State-Trait Anxiety Inventory (STAI-6) at pre-class, post-class and post-birth.ResultsFindings indicated significant improvements in childbirth self-efficacy expectancy, mental wellbeing, fear of childbirth, and both trait and state anxiety after attending the class, and these improvements remained stable until 4–8 weeks after birth. Women widely reported using relaxation practices, with the majority perceiving a positive influence on their pregnancy and childbirth experiences. The majority also viewed their overall childbirth experiences as positive.DiscussionConsequently, maternity services should consider reforming current antenatal education to align with these findings.